Global knowledge embeddedness - Holger Graf; Martin Kalthaus (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2022)
Various forms of interaction during the process of research and innovation constitute a global network of knowledge generation and diffusion. Countries and their research organizations and individual scientists need to be embedded in this network to participate in global knowledge ows and to increase success in idea generation, invention and innovation. In this chapter, we review the literature on two of the most important channels of international knowledge diffusion in the field of science: research collaboration and scientist mobility. We thereby focus on the motives and determinants to collaborate or move internationally, the formation of a global knowledge network and the effects of embeddedness in the network and its in uence on aggregate outcomes. From this review, we derive seven stylized facts on global knowledge embeddedness.
Keywords: O33; F60; O15; 330; scientist mobility; research collaboration; global knowledge network; literature review